Biobased Aliphatic Polyesters with DOPO Substituents for Enhanced Flame Retardancy - Pospiech, Doris; Korwitz, Andreas; Komber, Hartmut; Jehnichen, Dieter; Haeussler, Liane; Scheibner, Holger; Liebmann, Michael; Jaehnichen, Klaus; Voit, Brigitte (Macromolecular Chemistry and Physics, 2015)
Linear aliphatic copolyesters consisting of the biobased diols ethylene glycol, 1,3-propane diol, and 1,4-butane diol, the biobased dicarboxylic acids succinic acid, adipic acid, and sebacic acid, and a 9,10-dihydro-9-oxa-10-phospha-phenanthren-10-oxide (DOPO)-containing diol or dicarboxylic acid are presented. Structural characteristics of the new copolyesters are studied by 1H and 13C NMR spectroscopy. The influence of chemical composition on the property profile is examined evaluating glass transition temperature Tg, melting behavior, thermal degradation and combustion, mechanical and burning behavior. Incorporation of DOPO monomers suppresses crystallization and yields materials with reduced toughness except in case of sebacates. Tg rises with the content of DOPO monomer. Correlations between the number of methylene groups in the repeating unit and the thermogravimetric analysis degradation maximum, as well as the heat release capacity from pyrolysis combustion flow calorimeter reflect the systematic influence of chemical structure. Copolycondensation with DOPO monomers enhances the limiting oxygen index providing materials with improved overall value. Phosphorus-containing biobased copolyesters are prepared to improve the fire behavior of linear aliphatic polyesters. The incorporation of 9,10-dihydro-9-oxa-10-phospha-phenanthren-10-oxide substituents yields new materials with reduced heat release capacity and enhanced limiting oxygen index. Relations between structural features and degradation/combustion parameters are shown enabling the design of tailor-made flame retardants.
CRIS-Team Scopus Importer:2023-03-20
Keywords: biobased; degradation; flame retardance; phosphorus-containing; polyesters